Stem cell therapy: a potential for the perils of pancreatitis - Chela, Harleen; Romana, Bhupinder S.; Madabattula, Markandeya; Albarrak, Abdulmajeed A.; Yousef, Mohamad H.; Samiullah, Sami; Tahan, Veysel (Turkish Journal of Gastroenterology, 2020)
Acute and chronic pancreatitis carry a significant disease burden and there is no definite treatment that exists for either. They are associated with local and systemic inflammation and lead to numerous complications. Stem cell therapy has been explored for other disease processes and is a topic of research that has gained momentum with regards to implications for acute and chronic pancreatitis. They not only carry the potential to aid in regeneration but also prevent pancreatic injury as well as injury of other organs and hence the resultant complications. Stem cells appear to have immunomodulatory properties and clinical potential as evidenced by numerous studies in animal models. This review article discusses the types of stem cells commonly used and the properties that show promise in the field of pancreatitis.